Gold Nanoparticle-based Colorimetric Aptasensor for Detection of Malathion - TIAN Hengqi, WANG Yao, YANG Haitao, LI Zhaozhou, WU Jiabei, WANG Lin, LIU Haoyu, CHANG Yunhe, CHEN Xiujin (Shipin Kexue, 2023)
In this study, a novel colorimetric sensing method for the detection of malathion was established based on the principle that gold nanoparticles (AuNPs) can aggregate in high-salt solutions, leading to color changes in the solutions. The optimal concentration of NaCl was 500 mmol/L and the optimal concentration of aptamer was 1 μmol/L in the reaction system. This method showed a good linear relationship in the range of malathion concentration of 50–1 500 ng/mL, with a detection limit of 45.54 ng/mL. The recoveries of malathion in spiked lettuce and apple samples were 98.24%–100.91% and 99.48%–101.29%, respectively. The AuNPs-based colorimetric aptasensor could be used for the sensitive, specific, accurate and rapid detection of malathion. Furthermore, this study may provide a reference for developing colorimetric aptasensors for the detection of other pesticide residues.